Analysis of serious adverse events in a paediatric fast breathing pneumonia clinical trial in Malawi. Issue 1 (3rd September 2019) - Nkwopara, Evangelyn; Schmicker, Robert; Mvalo, Tisungane; Phiri, Melda; Phiri, Ajib; Couasnon, Mari; McCollum, Eric D.; Ginsburg, Amy Sarah
Abstract : Introduction: Pneumonia is the leading infectious killer of children. We conducted a double-blind, randomised controlled non-inferiority trial comparing placebo to amoxicillin treatment for fast breathing pneumonia in HIV-negative children aged 2–59 months in Malawi. Occurrence of serious adverse events (SAEs) during the trial were examined to assess disease progression, co-morbidities, recurrence of pneumonia and side effects of amoxicillin. Methods: Enrolled children with fast breathing for age and a history of cough <14 days or difficult breathing were randomised to either placebo or amoxicillin for 3 days, and followed for 14 days to track clinical characteristics and outcomes. Medical history, physical exam, laboratory results and any chest radiographs collected at screening, enrolment and during hospitalisation were evaluated. All SAE reports were reviewed for additional information regarding hospitalisation, course of treatment and outcome. Results: In total, 102/1126 (9.0%) enrolled children with fast breathing pneumonia were reported to have a SAE. Seventy-five per cent (n=77) of SAEs were pneumonia-related (p< 0.01). Children<2 years of age represented the greatest proportion (61/77, 79.2%) of those with a pneumonia-related SAE. In the amoxicillin group, there were 46 SAEs and 5 (10.9%) cases were identified as possibly related to study drug (4 gastroenteritis and 1 fever). There were no life-threatening pneumonia SAEs or deaths in either group, and by the time of exit from the study, all children recovered without sequelae. Discussion: In this fast breathing pneumonia clinical trial, SAEs occurred infrequently in both the amoxicillin and placebo groups, and amoxicillin was well tolerated. Trial registration number: NCT02760420 . https://clinicaltrials.gov/ct2/show/NCT02760420?term=ginsburg&rank=9 .